Exchange-Traded Funds (ETFs) Performance in Emerging Markets Before and After Financial Crisis - Tang, Mengxi (2015)
The purpose of this research is to investigate the return and volatility of five iShares MSCI emerging-market ETFs in comparison with iShares S&P500 (IVV) ETFs over the period from January 2003 to June 2015. The contribution of this research is giving investors a comprehensive analysis of ETFs in emerging markets by comparing the performance of ETFs in three periods including before, during, and after the financial crisis. In our analysis, we employ four approaches to discover the return characteristics and main source of volatility of emerging-market ETFs by analyzing volatility ratios, return and volatility correlations, asymmetric comovement and the impact on location of trade. Results indicate that emerging-market ETF returns are more volatile during exchange trading hours than during non-trading hours. The results of higher overnight volatility of Asian market ETFs and higher daytime volatility of American market ETFs provide evidence that the main source of volatility of emerging-market ETFs is public information released in each local market. Furthermore, during financial crisis, the emerging-market ETF returns are relatively stable and the correlations between emerging-market ETFs and U.S. market ETFs are significantly high. Moreover, there is no asymmetric comovement between emerging market ETFs and U.S. market ETFs in the complete sample period. In addition, U.S. market returns have a greater portion of emerging-market ETF returns than local market returns, especially in the period of financial crisis.